Ribosomal accretion, apriorism and the phylogenetic method: a response to Petrov and Williams - Caetano-Anollés, Derek; Caetano-Anollés, Gustavo (Frontiers in Genetics, 2015)
Historical (ideographic) and non-historical (nomothetic) studies of ribosomal accretion appear to arrive at diametrically opposite conclusions. Phylogenetic analysis of thousands of RNA molecules and protein structures in hundreds of genomes supports the structural origin of the ribosome in RNA decoding and ribosomal mechanics. Predictions from extant features in a handful of rRNA structural models of the large ribosomal subunit support its origin in protein biosynthesis. In recent correspondence, one of us reported that correcting dismissals of conflicting data and avoiding unwarranted assumptions of the nomethetic method reconciled conclusions. In response, Petrov and Williams dismissed our arguments claiming we did not understand their ‘BS’ algorithmic model of ribosomal apical growth. Instead, they controverted the historical approach. Here we show that their objections to the phylogenetic method are unjustified, that the BS algorithm subjectively guarantees back-in-time molecular deconstructions towards the protein biosynthetic core, and that processes of ribosomal growth are much more complex. We prompt abandoning apriorism, decreasing ad hoc hypotheses and integrating historical and non-historical scientific methods.